Accuracy of XCT to Perform Dimensional Measurements on Different Measurands - Obaton, Anne-Françoise; Tanich, Anis; Fischer, Nicolas; Antona, Sophie; Montagner, Florian; Genot, Sylvain; Brzuchacz, Sébastien; Soete, Patrick De; Duboeuf, Kevin; Beuvier, Thomas; Nanjareddy, Rakesh; Coutant, Nicolas; et al. (Science and Technology: Developments and Applications Vol. 1, 2024)
As additive manufacturing is increasingly used in industry to manufacture complex shapes with internal features, x-ray computed tomography (XCT) has become an essential tool for performing dimensional measurements. Thus, an x-ray computed tomography (XCT) interlaboratory comparison campaign, involving an aluminium-machined object, whose dimensions (92 × 78 × 63 mm3) are significant for a 225 kV XCT system, was performed for the purpose of investigating the performances of industrial XCT systems for dimensional measurements in terms of accuracy, i.e. precision and trueness, and to evaluate the influence of the measurement protocol (i.e. measurement strategy), of the operator and of the software on the results by comparison to reference measurements. The campaign involved seven French XCT users and system suppliers. Seven measurands were selected for the comparison campaign, including one distance, three diameters, one cylindricity, one coaxiality and one true position. The results of the comparison campaign were analysed to evaluate the performance of XCT systems implementing ISO 5725-2 related to accuracy, and more specifically to one of the two components of accuracy: precision, and ISO 5725-4 related to the other component of accuracy: trueness. In this campaign, we came to the conclusion that the measurement strategy is predominant, except for distance; that the measurement process is affected by the operator only for cylindricity and coaxiality; that there is no or little influence of the software except for coaxiality and position; and that a volumetric Gaussian filter allows improving the measurements only for some participants’ measurements. Furthermore, different behaviours, in terms of precision and trueness, are observed depending on the type of measurands when performed by different operators. The diameter measurements are reproducible with XCT, lower than 30 \(μ\)m which corresponds to a subvoxelic factor of 2.5 and the trueness is lower than 22 \(μ\)m. The distance measurement is also reproducible with XCT, 15 \(μ\)m which corresponds to a subvoxelique factor of 4.9 and the trueness is 8 \(μ\)m. For these measurands, their measurements do not depend on the used XCT system. However, the XCT reproducibility for cylindricity, coaxiality and position is worse as well as the trueness except for the position which has a trueness of 1 \(μ\)m. The process measurement should be revised regarding cylindricity and coaxiality measurements which have been done (see addendum). Finally, overall, the ability of the participants to perform measurements with XCT, whatever their system, is statistically comparable except for a few measurements. In this article, the results of an interlaboratory comparison campaign on XCT dimensional measurements have been presented.